2016
DOI: 10.1017/s0007114515005498
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protein-rich meals on glycaemic response of rice

Abstract: Asians typically consume carbohydrate-rich and high-glycaemic-index diets that have been associated with an increased risk of developing type 2 diabetes. Rice is rarely eaten alone such that it is of interest to investigate the effects of co-ingesting different protein-rich meals with rice on insulin and glycaemic response. This study had a randomised, controlled, non-blind, cross-over design in which fifteen healthy Chinese male participants were required to come on non-consecutive days. Five rice-based test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…In a series of studies that contained plant proteins dispensed as beverages, it has repeatedly been demonstrated that these proteins are insulinotropic and are therefore effective in reducing the glycemic response of foods [ 10 , 11 , 24 ]. The average amount of proteins in these beverages has been in the region of 12–24 g. In our present study, we have demonstrated that compared to 7.8 g of protein, a considerable reduction in the soy protein content (3.4 g) of a beverage but the inclusion of rice bran can elicit a similar reduction in the glycemic response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a series of studies that contained plant proteins dispensed as beverages, it has repeatedly been demonstrated that these proteins are insulinotropic and are therefore effective in reducing the glycemic response of foods [ 10 , 11 , 24 ]. The average amount of proteins in these beverages has been in the region of 12–24 g. In our present study, we have demonstrated that compared to 7.8 g of protein, a considerable reduction in the soy protein content (3.4 g) of a beverage but the inclusion of rice bran can elicit a similar reduction in the glycemic response.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids have been shown to stimulate gut peptides like glucagon-like peptide-1 (GLP-1), cholecystokinin (CCK) and peptide tyrosine tyrosine (PYY), and GLP-1, in particular, can increase early-phase insulin secretion [ 36 , 37 ]. Increased insulin has been found by our lab after ingestion of soymilk and amino acids from chicken essence [ 10 , 24 , 38 ]. In contrast, in this study, no increased insulin response was observed over two hours after the consumption of the soymilks as compared to the control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations